DEFINE PHASE ON THE DEVELOPMENT OF "SELF AND PEER EVALUATION" MODELS AT THE SUPERVISION OF SCIENCE LEARNING - Eny Winaryati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Define phase is the second phase after the analysis phase in theseries of research and development stage (R & D). Define Phase is the phase to determine the scope of project, planning, activities, evaluation, results,schedule, and deployment. This phase contains the defining activities prior to the proposed project. The stages ofdefine phase activities are as follows: 1) Information on model planning that needs to be developed; 2)Establishingthe benchmarks of success potential (assessment); 3) Preparation of paedagogical sides which needattention; 4) How to deliver model products to users; 5) Determining product proposal; 6) Planning a strategy todetermine the effectiveness of model. Each stage of Define Phase contains detailed descriptions of thedevelopment of Self and PeerEvaluation Models (EDTS) on the supervision of science learning. The data wereanalyzed using qualitative-descriptive approach. The object of this research was Self and Peer Evaluation ofScience Teachers (EDTS). The subject of this research was the science teachers of the junior high school;thepeer evaluation was the peer teachers; and the supervisor was the principal. The population was the State JuniorHigh Schools in Semarang city, and the sampleswere nine State Junior High Schools in Semarang City. Thesuggestion of this research was the need to develop the EDTS model plan in further R & D stages, particularly indesign phase. Keyword: define phase,  development, self and peer evaluation, edts models, supervision, science learning